2015
DOI: 10.1111/jon.12191
|View full text |Cite
|
Sign up to set email alerts
|

Optic Neuritis and the Visual Pathway: Evaluation of Neuromyelitis Optica Spectrum by Resting‐State fMRI and Diffusion Tensor MRI

Abstract: The rsfMRI detected cortical reorganization following ON attack, but WM was considerably preserved in the posterior VP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Resting-state fMRI has been used to explore the functional alterations in the brain in NMO and revealed reduced ALFF and increased synchronization in the visual cortex 6 7 . The rsFC measures the temporal coherence of BOLD signals between every two spatially remote regions or voxels and has been thought to reflect functional integration of the brain 26 27 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resting-state fMRI has been used to explore the functional alterations in the brain in NMO and revealed reduced ALFF and increased synchronization in the visual cortex 6 7 . The rsFC measures the temporal coherence of BOLD signals between every two spatially remote regions or voxels and has been thought to reflect functional integration of the brain 26 27 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Neuromyelitis optica (NMO) is characterized by optic nerve damage that may result in structural and functional alterations of the posterior visual pathways via Wallerian degeneration 1 2 3 4 . For example, NMO patients have shown reduced grey matter volume (GMV) 2 5 and altered spontaneous brain activity 6 7 in the visual cortex and impaired integrity in the optic radiation 3 4 5 8 9 10 11 12 13 14 .…”
mentioning
confidence: 99%
“…Presence of occult white matter damage as measured, for example, by DTI, MTR, or T1 relaxation time, has also remained contentious, presumably again owing to differences in inclusion criteria and different approaches to the correction for multiple comparisons problem (223)(224)(225)(226)(227)(228). Few functional imaging studies with resting state fMRI (rs-fMRI) in NMOSD suggest that visual impairment due to severe optic neuritis causes brain network connectivity changes, in particular in visual networks (229)(230)(231)(232). The vast majority of MR spectroscopy studies of the brain has found no clear indication for covert white matter damage (233)(234)(235)(236)(237), and low myoinositol/creatine values in the lesional cervical cord of NMOSD patients suggest astrocytic damage (238).…”
Section: Neuromyelitis Optica Spectrum Disorders (Nmosd)mentioning
confidence: 99%
“…Besides the involvement of optic nerve and spinal cord, gray matter (GM) abnormalities have been frequently reported in NMO. NMO patients have shown astrocyte damage and neuron loss in cerebral cortex in pathologic studies (Kawachi & Lassmann, ); altered neuronal activities in resting‐state fMRI studies (Cai et al, ; Liang et al, ; Liu et al, ; Liu et al, ; Lopes et al, ); and reduced gray matter volume (GMV) in structural MRI (Kim et al, ; Liu et al, ; Masuda et al, ; Wang, Zhang et al, ). Several of these alterations have been correlated with cognitive impairment in patients with NMO.…”
Section: Introductionmentioning
confidence: 99%